Kimia Persepsi Guru Kimia tentang Penilaian Kemampuan Berpikir Tingkat Tinggi - Resi Febriyanti; Endang Widjajanti (Postgraduate, University of Mataram, 2023)
Higher order thinking skills are an assessment that must be integrated into 2013 Curriculum learning process. The purpose of this study is to investigate the chemistry teacher’s perception about higher order thinking skills assessment. Descriptive qualitative was used in this study. This study implicated 10 chemistry teacher from 10 senior high school in West Kalimantan. Data on chemistry teacher’s perception about higher-order thinking skills assessment were obtained from questionnaire consist of 10 questions. The results showed that most of the chemistry teachers in West Kalimantan already know and implement higher order thinking skills assessment in learning, like final exam and daily test. The HOTS assessment has been implemented by most teachers, but the implementation was not optimal even though in terms of knowledge all teachers already know about the HOTS assessment.